Dynamics of the cardioelectric field of rats under chronic exposure to doxorubicin during atrial depolarization - S. L. Smirnova; O. V. Suslonova; I. M. Roshchevskaya (Фармакокинетика и Фармакодинамика, 2022)
The aim of the work is non-invasive identification of the features of the initial atrial activity by the dynamics of the cardioelectric field on the surface of the chest of experimental animals under chronic exposure to doxorubicin. Materials and methods. The distribution and dynamics of changes in cardioelectric potentials on the surface of the chest of rats under chronic exposure to doxorubicin during the period of initial atrial activity were investigated. Doxorubicin was administered intraperitoneally 1.5 mg/kg once a week for a month. The cumulative dose was 6 mg/kg animal weight. Results. It has been shown that chronic exposure to doxysubicin leads to changes in the positional dynamics of positive and negative cardiopotentials cardioelectric field of heart on the chest surface during the ascending and descending P-wave on the ECG in the II limb leads. It is observed significantly earlier the beginning of cardioelectric field formation, characteristic of atrial depolarization, on the body surface, the beginning, the peak and the end of the P-wave on the ECG in the II limb leads compared to the initial state. Conclusion. Chronic exposure to doxorubicin causes significant changes in the initial atrial activity, which leads to a significant change in the corresponding period of atrial depolarization in the dynamics of the cardioelectric field on the surface of the thorax of animals.